Modular Biomicrofluidics - Mikrofluidikchips im Baukastensystem für Anwendungen aus der Zellbiologie - Kreppenhofer, Kristina (Schriften des Instituts für Mikrostrukturtechnik am Karlsruher Institut für Technologie / Hrsg.: Institut für Mikrostrukturtechnik, 2013)
The present work shows the development, optimization and application of biomicrofluidic chips. The developed microfluidic chios are used to (1) analyze the stem cell differentiation, (2) produce valuable substances via metabolic engineering and (3) the fabrication of polymeric films possessing a gradient of morphology. All structures are build up from two elementary structures and all microstructured parts are normalized to the size of a microscope glass slide.